Adapting the Service-Learning Program into the Educational Process (Case Study of U.S. Colleges) - Сарсенбаев, Ақылбек; Абдирайымова , Ардақ; Жұмаш, Гаухар (Pedagogy and Psychology, 2023)
Abstract The article discusses the basic concepts of the program - social work and its connections with other areas at the interdisciplinary level. It also describes the relationship of community service to public service and basic research, its theoretical foundation, its formation and development as a discipline, how it differs from other disciplines, and its practical application. Teachers are provided with information and resources on the discipline of Service Learning that they can integrate into their existing education system. To serve the community, the equation of "learn - make choices - serve" must be followed. Because the article was prepared using foreign sources, it has advantages for educators and researchers who do not have access to resources but are interested in the issue and seek to adapt the discipline into the educational process. Key words: pedagogy, conscientious service to society, volunteering, public organizations, university students, service learning, academic environment, state and non-state organizations, social groups, interdisciplinary relations.